The Role of the Interrogative Model in Teaching English via the Communicative Approach (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides an in-depth analysis of how the interrogative model can support and enhance the communicative approach in teaching English. The effective teaching of English as a second language (ESL) has increasingly emphasized communicative competence, which involves not only the mastery of grammatical rules but also the ability to use language effectively in real-life situations. This article explores the role of the interrogative model in enhancing language learning within the framework of the communicative approach. The interrogative model, based on the strategic use of questions, fosters active student participation, critical thinking, and deeper understanding. In conjunction with the communicative approach, this model enhances students’ language proficiency by encouraging interactive, real-world communication and problem-solving